Effect of Various Electronic Devices on the Performance of Electronic Apex Locator - Parirokh, Masoud; Manochehrifar, Hamed; Abbott, Paul V.; Borna, Roya; Haghdoost, Ali Akbar (Iranian Endodontic Journal, 2019)
Introduction: Apex locators are important devices that can be used to determine working length during root canal treatment. However, it is not known whether electronic devices with various wave length frequencies influence the accuracy of apex locators. The aim of this study was to determine whether a cordless phone set, MP4 player, FM radio, asymmetric digital subscriber line (ADSL), or a mobile phone could influence the accuracy of working length determination by the Dentaport ZX apex locator. Methods and Materials: In this study, twenty-four sound intact single-rooted extracted human teeth were used. After determining the root canal length with a file and a microscope, the canals were measured with three separate Dentaport ZX apex locators while one of the test devices (ADSL, MP4, FM radio, mobile phone, and cordless phone) was used at a distance of 50 cm from the apex locator. Bland–Altman plots was used for reliability and consistency. Results: Except for the FM radio, all other devices showed significant difference with actual working length (P<0.05). ADSL and MP4 player showed the least consistency compared to the other devices. Conclusion: Based on this in vitro study, the use of ADSL, MP4 player, mobile phone, and cordless phone during root canal treatment may influence working length determination with the Dentaport ZX apex locator. Keywords: ADSL; Apex Locator; Cell Phone; Dentaport ZX Apex Locator; MP4 Player; Radio; Wave Length